A comparison of non-invasive imaging modalities: Infrared thermography, spectrophotometric intracutaneous analysis and laser Doppler imaging for the assessment of adult burns. Issue 8 (December 2015) - Burke-Smith, Alexandra; Collier, Jonathan; Jones, Isabel
Highlights: Scanoskin™ can be used to predict burn wound healing time. Thermal imaging is less reliable due to evaporative water losses. Scanoskin™ and thermal imaging are both cheaper and easier to use than LDI. Scanoskin™ images are harder to interpret due to a monochrome palette. Further work is needed to establish whether Scanoskin™ can replace LDI in due course. Abstract: Background: Currently, the only evidence-based adjunct to clinical evaluation of burn depth is laser Doppler imaging (LDI), although preliminary studies of alternative imaging modalities with instant image acquisition are promising. This is a study to investigate the accuracy of infrared thermography (IRT) and spectrophotometric intracutaneous analysis (SIA) for burn depth assessment, and compare this to the current gold standard: LDI. We include a comparison of the three modalities in terms of cost, reliability and usability. Methods: We recruited 20 patients with burns presenting to the Chelsea and Westminster Adult Burns Service. Between 48 h and 5 days afterburn we recorded imaging using moorLDI2-BI-VR (LDI), FLIR E60 (IRT) and Scanoskin™ (SIA). Subsequent clinical management and outcome was as normal, and not affected by the extra images taken. Results: 24 burn regions were grouped according to burn wound healing: group A healed within 14 days, group B within 14–21 days, and group C took more than 21 days or underwent grafting. Both LDI and IRT accurately determined healing potential in groups A and C, but failed to distinguish between groups B and C ( p > 0.05). Scanoskin™ interpretation of SIA was 100% consistent with clinical outcome. Conclusion: FLIR E60 and Scanoskin™ both present advantages to moorLDI2-BI-VR in terms of cost, ease-of-use and acceptability to patients. IRT is unlikely to challenge LDI as the gold standard as it is subject to the systematic bias of evaporative cooling. At present, the LDI colour-coded palette is the easiest method for image interpretation, whereas Scanoskin™ monochrome colour-palettes are more difficult to interpret. However the additional analyses of pigment available using SIA may help more accurately indicate the depth of burn compared with perfusion alone. We suggest development of Scanoskin™ software to include a simplified colour-palette similar to LDI and additional work to further investigate the potential of SIA as an alternative to the current gold standard.